Excellent supercapacitor and sensor performance of robust cobalt phosphinate ferrocenyl organic framework materials achieved by intrinsic redox and structure properties. Issue 45 (6th November 2019) - Khrizanforov, Mikhail; Shekurov, Ruslan; Miluykov, Vasily; Gilmanova, Leysan; Kataeva, Olga; Yamaleeva, Zilya; Gerasimova, Tatiana; Ermolaev, Vadim; Gubaidullin, Aidar; Laskin, Artem; Budnikova, Yulia
Abstract : A new Co coordination polymer with phosphinates and Fc fragments was synthesized, which can be used as a water sensor and sorbent and also as a supercapacitor electrode. Abstract : A new redox active coordination polymer [Co(H2 O)2 (Fc(PHOO)2 )·2H2 O] n (Fc = ferrocene) was synthesized by the diffusion method and characterized by single-crystal X-ray diffraction. Phosphinate fragments formed infinite chains connected through ferrocene fragments to 2D PCP associated with cobalt atoms. Additional strong hydrogen bonding via the participation of coordinated and lattice water molecules resulted in the formation of a 3D network. The polymer exhibited water-induced crystal-to-amorphous transformation with chromotropism, as confirmed by spectroscopic techniques, elemental analysis, TGA and XRPD. The explosion of the amorphous phase [Co(Fc(PHOO)2 )] n to form water vapor readily led to its conversion into the initial crystalline [Co(H2 O)2 (Fc(PHOO)2 )·2H2 O] n with a reverse change of color. The dehydrated form of the polymer selectively sorbed water and could be used as a material with the function of an express dehydrator. Moreover, a modified electrode could qualitatively determine the water content in the solvent at a concentration of 0.05%. Both hydrated and dehydrated forms were evaluated as electrode materials for supercapacitors. The [Co(Fc(PHOO)2 )] n (dehydrated form) electrode exhibited high specific capacitance and excellent cycling stability. Its maximum specific capacitance was 2517 F g −1 at a current density of 2 A g −1, and the specific capacitance retention was about 90.1% after 1000 cycles.